Why do human and non-human species conceal mating? The cooperation maintenance hypothesis. Issue 1932 (5th August 2020) - Ben Mocha, Yitzchak
Abstract : Despite considerable cultural differences, a striking uniformity is argued to exist in human preferences for concealing sexual intercourse from the sensory perception of conspecifics. However, no systematic accounts support this claim, with only limited attempts to understand the selective pressures acting on the evolution of this preference. Here, I combine cross-cultural and cross-species comparative approaches to investigate these topics. First, an analysis of more than 4572 ethnographies from 249 cultures presents systematic evidence that the preference to conceal mating is widespread across cultures. Second, I argue that current anthropological hypotheses do not sufficiently explain why habitual concealment of mating evolved in humans but is only seldom exhibited by other social species. Third, I introduce the cooperation maintenance hypothesis, which postulates that humans, and a specific category of non-human species, conceal matings to prevent sexual arousal in witnesses (proximate explanation). This allows them to simultaneously maintain mating control over their partner(s) and cooperation with group members who are prevented from mating (ultimate explanations). I conclude by presenting a comparative framework and predictions to be tested across species and human cultures.